Circulating serotonin levels in COPD patients: a pilot study - Pietro Pirina; Elisabetta Zinellu; Panagiotis Paliogiannis; Alessandro G. Fois; Viviana Marras; Salvatore Sotgia; Ciriaco Carru; Angelo Zinellu (BMC Pulmonary Medicine, 2018)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a major and increasing global health problem. Serotonin is a neurotransmitter that participates in several pulmonary functions and it has been involved in oxidative stress, which plays essential roles in the pathogenesis of COPD. The current study aimed at establishing the levels of circulating serotonin in COPD, and investigating eventual relations between serotonin and oxidative stress markers. Methods Whole blood serotonin was assessed in 43 consecutive patients with stable COPD and in 43 age and sex-matched healthy controls. Results Serotonin blood levels were significantly higher in COPD patients than in controls (median 0.81 μmol/L, IQR: 0.61–4.02 vs 0.65 μmol/L, IQR: 0.53–1.39, p = 0.02). The univariate logistic regression analysis evidenced that serotonin levels are independently associated with presence of COPD (crude OR = 7.29, 95% CI: 1.296–41.05, p = 0.003) and such an association was confirmed also after adjusting for several confounders (OR 21.92, 95% CI 2.02–237.83; p = 0.011). Conclusions Our study showed higher levels of circulating serotonin in COPD and an inverse correlation with the worsening of airway obstruction. Future studies are necessary to investigate the clinical utility of this finding.